Reduction of IL-17A Might Suppress the Th1 Response and Promote the Th2 Response by Boosting the Function of Treg Cells during Silica-Induced Inflammatory Response In Vitro - Wen Tang; Fangwei Liu; Ying Chen; Laiyu Song; Wujing Dai; Chao Li; Dong Weng; Jie Chen (Hindawi Limited, 2014)
Silica inhalation can induce chronic lung inflammation and fibrosis. Upon silica stimulation, activated macrophages trigger the T-lymphocyte which can differentiate into many different types of Th cells, including the recently discovered Th17 cells. IL-17A, the typical Th17 cytokine, is reported in some inflammatory diseases. However, the role of IL-17A in silica-induced inflammatory response is still not clear. The regulatory mechanism of silica-induced Th17 response also needs to be investigated. So we established a mice primary cell coculture system (macrophage and lymphocyte) to investigate the role of IL-17A in silica-induced inflammatory response in vitro, by using anti-IL-17A mAb and IL-1Ra. Both anti-IL-17A mAb and IL-1Ra decreased the level of IL-17A and increased the function of Treg cells. The Th1 response was suppressed and the Th2 response was promoted by the addition of anti-IL-17A mAb or IL-1Ra. IL-1Ra treatment decreased the level of IL-6, whereas the levels of IL-23 and ROR-γt were increased. Our study demonstrated that IL-17A reduction altered the pattern of silica-induced Th responses by boosting the function of Treg cells in vitro. Blocking the function of IL-1 signal pathway could suppress the level of IL-17A, which played the major role in modulating silica-induced Th responses in vitro.